Penyebab Kejadian Kekurangan Energi Kronis pada Ibu Hamil Risiko Tinggi dan Pemanfaatan Antenatal Care di Wilayah Kerja Puskesmas Jelbuk Jember - Christyana Sandra (Jurnal Administrasi Kesehatan Indonesia, 2018)
Background: The main cause of maternal death from 2010 to 2013 were bleeding, hypertension, infection, old labor, and abortion. From 2013 to 2015, public health center of Jelbuk had 50% high-risk pregnant women more than total pregnancy. Aim: The objective of this study was to identify factors of chronic energy loss incidence in high-risk pregnant women and service utilization of antenatal in Jelbuk public health center, Jember district. Method: This research was an analytic research with cross-sectional approach. The population of this study was all high-risk mothers who experienced Chronic Energy Deficiency or Kekurangan Energi Kronis (KEK) in the work area of Jelbuk public health center with a total sample of 42 respondents selected by using simple random sampling. Results: Results showed that most respondents had a complete use of ANC. There was a correlation between predisposing factors including age, knowledge, attitude and trust toward ANC utilization. There was no correlation between supporting factors including the variable of access to health service and officers’ services with ANC utilization. There was a correlation between need factors (mother’s health condition) with ANC utilization. Conclusion: Overall, the respondents had completed Antenatal Care (ANC). The predisposing factors (age, knowledge, behavior, and trust) was correlated to the use of ANC, but the supporting factors was not correlated to ANC utilization. It is recommended to promote ANC to pregnant mothers with Chronic Energy Loss and strengthen cadres’ performance for socialization.